2008
DOI: 10.5194/angeo-26-2871-2008
|View full text |Cite
|
Sign up to set email alerts
|

On a new process for cusp irregularity production

Abstract: Abstract. Two plasma instability mechanisms were thought until 2007 to dominate the formation of plasma irregularities in the F region high latitude and polar ionosphere; the gradient-drift driven instability, and the velocity-shear driven instability. The former mechanism was accepted as accounting for plasma structuring in polar cap patches, the latter for plasma structuring in polar cap sun aligned arcs. Recent work has established the need to replace this view of the past two decades with a new patch plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 29 publications
2
50
0
Order By: Relevance
“…Among other things, recent experimental studies of F region plasma waves have examined the observed irregularity formation times and compared them with those predicted by the F region instability theories including GDI and the Kelvin‐Helmholtz instability (KHI) [ Kintner and D'Angelo , ]. The results varied between being significantly faster than GDI predictions [ Moen et al , ; Carlson et al , , ] and being largely consistent with GDI [ Oksavik et al , ]. The first group of results is explained by invoking the KHI process.…”
Section: Discussionmentioning
confidence: 99%
“…Among other things, recent experimental studies of F region plasma waves have examined the observed irregularity formation times and compared them with those predicted by the F region instability theories including GDI and the Kelvin‐Helmholtz instability (KHI) [ Kintner and D'Angelo , ]. The results varied between being significantly faster than GDI predictions [ Moen et al , ; Carlson et al , , ] and being largely consistent with GDI [ Oksavik et al , ]. The first group of results is explained by invoking the KHI process.…”
Section: Discussionmentioning
confidence: 99%
“…The velocity shear seen in the SuperDARN data (Figures i and j) could drive the Kelvin‐Helmholtz (KH) instability. The KH growth rate can be estimated by γ KH =0.2 Δ V / L where Δ V is the velocity difference and L is the scale length of the velocity difference [ Carlson et al , ]. Based on the velocity data shown in Figure j, the KH growth time can be estimated to ∼70 min, which indicates the KH instability is not effective.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the GDI occurs initially on the trailing edge, the nonlinear development could penetrate through the entire patch (Gondarenko & Guzdar 2004). The plasma can also be structured throughout a patch upon its formation, formed either by a magnetic reconnection event which of itself introduces sheer driven instabilities (Carlson et al 2008), or by soft-electron precipitation (Kelley et al 1982). In addition, the patches may follow a nonuniform flow pattern which can be highly dynamic and pulsed.…”
Section: Discussionmentioning
confidence: 99%
“…Within the auroral zone there is a lot of free energy to drive various instabilities. Obviously, there may be velocity shears associated with auroral arcs that can rapidly develop small scale irregularities on large scale structures (auroral blobs) by the KelvinHelmholtz type, velocity shear Instability (KHI) (Kersley et al 1988;Keskinen et al 1988;Carlson et al 2008;Carlson 2012). The auroral precipitation interacting with the polar cap patches may give rise to plasma gradients on which the GDI can operate as has been documented in the dayside cusp (Moen et al 2012).…”
Section: Discussionmentioning
confidence: 99%